2017
DOI: 10.20965/jaciii.2017.p0616
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Style Classification Based on Ensemble Learning and Adaptive Feature Value by Using Inertial Measurement Unit

Abstract: We have been constructing a swimming ability improvement support system. One of the issues to be addressed is the automatic classification of swimming styles (backstroke, breaststroke, butterfly, and front crawl). The mainstream swimming style classification technique of conventional researches is based on non-ensemble learning; in their classification, breaststroke and butterfly are mixed up with each other. To improve its generalization performance, we need to use better classifiers and more adaptive feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Furthermore, Ref. [ 58 ] showed that combining several consecutive predictions led to 100% good predictions. More recently, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ref. [ 58 ] showed that combining several consecutive predictions led to 100% good predictions. More recently, Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inter-cyclic variation is another important factor (Barbosa et al, 2005;Figueiredo et al, 2012) which might cause error in technique identification, which was not examined in this study. Our method, however, presents a higher accuracy in comparison to reported result in the literature based on sacrum sensor (Davey et al, 2008;Omae et al, 2017). Some studies use a network of IMUs (Wang et al, 2016) or a smartphone (Pan et al, 2016) for swimming technique identification while we focused on each sensor location separately.…”
Section: Macro Analysismentioning
confidence: 69%
“…To evaluate how our proposed method is an improved solution, we have solved the same problem using existing feature space evaluation indices such as BW-Ratio [7], OOB [8], ReliefF [9], and Minimum Reference Set (MRS) [10]. Among the existing feature space evaluation indices, BW-Ratio, ReliefF, and OOB are widely used as general methods for selecting features, and are believed to [11,12], OOB, in References [13,14], and Reli-efF, in References [15,16]). In contrast, MRS selects features using a small amount of training data, which is one of the aims of this paper.…”
Section: Experimental Purpose and Outlinementioning
confidence: 99%